The design and optimization of RNA trans‐splicing molecules for skin cancer therapy. Issue 6 (19th August 2013) - Gruber, Christina; Koller, Ulrich; Murauer, Eva M.; Hainzl, Stefan; Hüttner, Clemens; Kocher, Thomas; South, Andrew P.; Hintner, Helmut; Bauer, Johann W.
Abstract : Targeting tumor marker genes by RNA trans‐splicing is a promising means to induce tumor cell‐specific death. Using a screening system we designed RNA trans‐splicing molecules (RTM) specifically binding the pre‐mRNA of SLCO1B3, a marker gene in epidermolysis bullosa associated squamous cell carcinoma (EB‐SCC). Specific trans‐splicing, results in the fusion of the endogenous target mRNA of SLCO1B3 and the coding sequence of the suicide gene, provided by the RTM. SLCO1B3‐specific RTMs containing HSV‐tk were analyzed regarding their trans‐splicing potential in a heterologous context using a SLCO1B3 expressing minigene (SLCO1B3‐MG). Expression of the chimeric SLCO1B3‐tk was detected by semi‐quantitative RT‐PCR and Western blot analysis. Cell viability and apoptosis assays confirmed that the RTMs induced suicide gene‐mediated apoptosis in SLCO1B3‐MG expressing cells. The lead RTM also showed its potential to facilitate a trans‐splicing reaction into the endogenous SLCO1B3 pre‐mRNA in EB‐SCC cells resulting in tk‐mediated apoptosis. We assume that the pre‐selection of RTMs by our inducible cell‐death system accelerates the design of optimal RTMs capable to induce tumor specific cell death in skin cancer cells. Highlights: The marker gene SLCO1B3 can be targeted by RNA trans‐splicing molecules (RTMs). Accurate RNA trans‐splicing leads to the fusion of SLCO1B3 and HSV‐thymidine kinase. Screening system accelerates the construction of RTMs with improved functionality. The expression of the SLCO1B3‐HSV‐tk fusion protein induces apoptosis in target cells.